Kesiapan Guru Bahasa Indonesia Sekolah Menengah Kejuruan (SMK) dalam Menghadapi Program Merdeka Belajar - Imrotin Imrotin; Ifit Novita Sari (Jurnal Guru Indonesia, 2022)
AbstractMerdeka Belajar is a program that has been launched by the Ministry of Education and Culture since 2019. Teachers as part of the learning system are expected to always be ready for changes in the educational order, including being the independent learning mover (penggerak merdeka belajar). This study aimed to determine the readiness of Indonesian language teachers at the Vocational High School (SMK) level in implementing the Guru Merdeka Belajar program. The discussion review consisted of three domains of the learning process, namely: planning; implementation; and evaluation of learning. Research informants were Indonesian language teachers at the SMK level, both public and private, in the Batu City area, East Java, totaling 10 people who were selected by snowball purposive sampling. Data was collected via Google Form with open-ended questions and interviews via WhatsApp. Data analysis used the Miles and Huberman model with the stages of data reductions, data presentation, and drawing conclusions. The results showed that: 1) teachers are ready to implement independent learning programs in the aspect of presenting material independently, involving students in apperception, becoming facilitators during learning, encouraging students to seek various learning resources, and being willing to receive feedback; 2) teachers are not ready in the aspect of designing objectives, methods, media, assessment tools, assessments, and follow-up feedback. AbstrakMerdeka belajar merupakan program yang dicanangkan oleh Kementerian Pendidikan dan Kebudayaan sejak tahun 2019. Guru sebagai bagian dari sistem pembelajaran diharapkan selalu siap dengan perubahan tatanan pendidikan, termasuk menjadi penggerak merdeka belajar. Penelitian ini bertujuan untuk mengetahui kesiapan guru Bahasa Indonesia jenjang SMK dalam melaksanakan program Guru Merdeka Belajar. Tinjauan pembahasan terdiri dari tiga ranah proses pembelajaran yakni: perencanaan; pelaksanaan; dan evaluasi pembelajaran. Informan penelitian adalah guru Bahasa Indonesia jenjang SMK baik negeri maupun swasta di wilayah Kota Batu, Jawa Timur berjumlah 10 orang yang dipilih secara snowball purposive sampling. Data dikumpulkan melalui Google Form dengan pertanyaan terbuka dan wawancara melalui WhatsApp. Analisis data menggunakan model Miles and Huberman dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: 1) guru siap melaksanakan program merdeka belajar dalam aspek penyajian materi secara mandiri, melibatkan siswa dalam apersepsi, menjadi fasilitator selama pembelajaran, mendorong siswa mencari berbagai sumber belajar, dan bersedia menerima umpan balik; 2) guru kurang siap dalam aspek perancangan tujuan, metode, media, alat penilaian, penilaian, dan tindak lanjut umpan balik.